2021
DOI: 10.7759/cureus.17243
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Willingness to Vaccinate Their Children Against COVID-19 in Saudi Arabia: A Cross-Sectional Survey

Abstract: BackgroundIn early 2021, vaccination against COVID-19 became one of the most important measures needed to control the pandemic. ObjectivesThis study aimed to investigate the levels of acceptance and factors affecting the decisions among Saudi parents and caregivers of children under 12 for getting them vaccinated. Design and settingA cross-sectional survey of 1000 caregivers and parents was carried out from May 2021 to June 2021. The participants were from the eastern, central, southern, western, and northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 9 publications
(20 reference statements)
2
21
2
2
Order By: Relevance
“… Yes [Y], unsure [U], no [N] Yes: 55.5 Unsure: 35.9 No: 8.6 ( Aldakhil et al, 2021 ) It is likely that I will vaccinate my child/children against COVID-19 in the next 6 months Strongly agree [Y], agree [Y], neutral [U], disagree [N], strongly disagree [N] Yes: 52.5 Unsure: 27.9 No: 19.6 ( Alfieri et al, 2021 ) If a new vaccine against COVID-19 became available, how likely would you be to get your child vaccinated? Very likely [Y], somewhat likely [Y], I'm not sure [U], not likely [N] Yes: 33.0 Unsure: NR No: NR ( Almusbah et al, 2021 ) Are you willing to get the COVID-19 vaccine for your child if approved? Yes [Y], unsure [U], no [N] Yes: 25.6 Unsure: 37.0 No: 37.4 ( Altulaihi et al, 2021 ) If a COVID-19 vaccine is available, will you vaccinate for your child?…”
Section: Resultsmentioning
confidence: 99%
“… Yes [Y], unsure [U], no [N] Yes: 55.5 Unsure: 35.9 No: 8.6 ( Aldakhil et al, 2021 ) It is likely that I will vaccinate my child/children against COVID-19 in the next 6 months Strongly agree [Y], agree [Y], neutral [U], disagree [N], strongly disagree [N] Yes: 52.5 Unsure: 27.9 No: 19.6 ( Alfieri et al, 2021 ) If a new vaccine against COVID-19 became available, how likely would you be to get your child vaccinated? Very likely [Y], somewhat likely [Y], I'm not sure [U], not likely [N] Yes: 33.0 Unsure: NR No: NR ( Almusbah et al, 2021 ) Are you willing to get the COVID-19 vaccine for your child if approved? Yes [Y], unsure [U], no [N] Yes: 25.6 Unsure: 37.0 No: 37.4 ( Altulaihi et al, 2021 ) If a COVID-19 vaccine is available, will you vaccinate for your child?…”
Section: Resultsmentioning
confidence: 99%
“…In nine studies [16,[18][19][20][21][22][23][24][25], participants with a high school or lower degree were less likely to accept COVID-19 vaccination for their children compared to those with college or higher education, while the opposite results were found in the other six studies [26][27][28][29][30][31]. Compared to women, men were more likely to accept the vaccination in ten studies [22,24,25,[27][28][29][32][33][34][35]. However, women's acceptance rate was higher in the studies of Babicki and Wan [36,37].…”
Section: Determinant Assessmentmentioning
confidence: 88%
“…Specifically, the novelty and side effects of COVID-19 vaccines were the two main concerning issues. During the pandemic, some vaccine candidates have been granted fast-track licensure by the US Food and Drug Administration [32], which may result in vaccination hesitancy. A considerable number of vaccine-hesitant parents cited mistrust with the rushed nature of testing in Hetherington's study [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teasdale et al reported that 49.4% of parents in the United States were willing to vaccinate their children younger than 12 years against COVID-19 [ 29 ]. Meanwhile, Almusbah et al reported that only 25.6% of parents in Arab were willing to do so [ 30 ]. Another study by Hetherington et al reported that 60.4% of mothers in Canada were keen to obtain the COVID-19 vaccine for their children aged 9–12 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%